2020
DOI: 10.1186/s12870-020-02727-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, validation, and cross-species transferability of EST-SSR markers developed from Lycoris aurea and their application in genetic evaluation of Lycoris species

Abstract: Background The Lycoris genus includes many ornamentally and medicinally important species. Polyploidization and hybridization are considered modes of speciation in this genus, implying great genetic diversity. However, the lack of effective molecular markers has limited the genetic analysis of this genus. Results In this study, mining of EST-SSR markers was performed using transcriptome sequences of L. aurea, and 839 primer pairs for non-redundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Advances in high-throughput sequencing technology and reduced sequencing costs have enhanced the efficiency and convenience of using transcriptomics data to identify SSR loci with large numbers of polymorphisms 32 . Compared with genomic-SSR molecular markers, EST-SSR molecular markers have lower development costs, greater versatility and conservation, and favorable associations with phenotypic traits 33 . In the present study, www.nature.com/scientificreports/ 2,510 SSR loci were identified from 37,538 unigenes in the A. heimuer transcriptome; the SSR frequency of 6.69% was higher than the rates for edible mushrooms such as Auricularia polytricha (4.70%) and Pleurotus eryngii (3.09%) 34,35 , indicating that the A. heimuer transcriptome contains abundant SSR loci.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in high-throughput sequencing technology and reduced sequencing costs have enhanced the efficiency and convenience of using transcriptomics data to identify SSR loci with large numbers of polymorphisms 32 . Compared with genomic-SSR molecular markers, EST-SSR molecular markers have lower development costs, greater versatility and conservation, and favorable associations with phenotypic traits 33 . In the present study, www.nature.com/scientificreports/ 2,510 SSR loci were identified from 37,538 unigenes in the A. heimuer transcriptome; the SSR frequency of 6.69% was higher than the rates for edible mushrooms such as Auricularia polytricha (4.70%) and Pleurotus eryngii (3.09%) 34,35 , indicating that the A. heimuer transcriptome contains abundant SSR loci.…”
Section: Discussionmentioning
confidence: 99%
“…In A. humile , 85% of the 14 tested cashew SSRs amplified ( Soares et al., 2013 ); in A. microcarpum , A. pumilum , and A. nanum , 92% of the 12 cashew SSRs amplified ( Croxford et al., 2006 ); and in A. microcarpum and A. othonianum , 100% of 54 transcriptome-based SSRs amplified ( Savadi et al., 2022a ). The relatively lower rate of transferability of genomic SSRs compared to genic SSRs could be attributed to the higher conservation of genic sequences compared to sequences from the anonymous regions of the genomes ( Ellis and Burke, 2007 ; Jiang et al., 2020 ). Thus, we contemplate that the SSR markers developed in this study can be a potential marker repository for not only cashew but also the related Anacardium species and could be employed for macro-syntenic comparisons, germplasm characterizations, genetic mapping, molecular breeding involving interspecies hybridizations, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical transferability described here has a significant potential to help genetic mapping, comparative genomics, and transferability studies as it can 'filter' large amounts of molecular information before experimental steps. Jiang et al (2020) reported that the increase in the number of species sequenced by NGS technologies would increase the information in databases such as GenBank, providing abundant material to be explored using BLAST-like tools. Theoretical transferability may be applied to any marker.…”
Section: Discussionmentioning
confidence: 99%